Herramientas que apoyan gestión de las expropiaciones de bienes inmuebles en proyectos viales - Parajeles-Mora, Anthony (Instituto Tecnológico de Costa Rica, 2016)
The main purpose of this Project was to develop tools that could support the management in expropriations of real estate goods in vial projects. As we know, the issue of expropriations makes one of the main obstacles so that public work projects can develop in an agile manner, consequently for the legal terms as for the administrative ones of the involved buildings. The previous is due to, in great measure, to the fact that one cannot count on a guide that offers details on how to work on a collection of information necessary in order to manage expropriations in an appropriate manner. Furthermore, this guide is necessary to know the flow of the actualized process of expropriation and to establish recommendations and good practices to support daily tasks in order to achieve expropriations projects in a settled, planned and good form. One of the tools needed would be a cadastral mosaic using the Geographical Information Systems (GIS) with recorded cadastral information, necessary and actualized, so that in the end one can relay with a tool that supports the management of expropriations with the benefits of carrying out public work projects in prudent terms. The previous looks to concentrate centralized and organized information in one system as well as a series of products that derived from it.
Proyecto de Graduación (Maestría en Ingeniería Vial) Instituto Técnologico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Expropiación; Guía; Herramientas; Proyectos; Vía; SIG